Horn Fly Control and Growth Implants are Effective Strategies for Heifers Grazing Flint Hills Pasture - S. S. Trehal; J. L. Talley; K. D. Sherrill; T. Spore; R. N. Wahl; W. R. Hollenbeck; Dale Blasi (Kansas Agricultural Experiment Station Research Reports, 2017)
Horn flies (Haematobia irritans(L.)) are considered the most important external parasite that negatively affects pasture-based beef systems with losses estimated to exceed 1 billion annually to the U.S. beef industry. Control strategies have relied heavily on insecticide applications to control horn flies and are implemented when the economic threshold of 200 flies/animal have been exceeded. When horn fly populations are maintained below 200 flies/animal by treating them with insecticides then the level of stress annoyance behaviors such as leg stomping, head throwing, and skin twitching decreases while grazing increases. While most stocker operators utilize some type of fly control these are rarely used as a single pharmaceutical technology to aid in performance of the animals. Additional pharmaceutical technologies are utilized in combination of others, with the use of de-wormers and implants showing the largest impact with performance of stockers. The objective of this study was to compare a commercial injectable insecticide, LongRange, to an insecticidal ear tag for horn fly control and determine the impact of weight performance on stockers when fly control technologies were used in combination with implants versus no implants.
Keywords: horn fly; implants; LongRange